Pemodelan Hidrodinamika Aliran dan Transportasi Sedimen pada Ruas Pertemuan Sungai Citarum Hilir dan Cibeet, Jawa Barat - Suryadi, Yadi; Siregar, Ruth Helena; Harlan, Dhemi; Samskerta, I Putu (Direktorat Bina Teknik Sumber Daya Air, Kementerian Pekerjaan Umum dan Perumahan Rakyat, 2024)
Flooding and changes in riverbed morphology often become issues near river confluences, as observed at the confluence of Citarum Hilir and Cibeet Rivers. This study aims to analyze the cross-sectional capacity and riverbed changes around the confluence of Citarum Hilir and Cibeet Rivers. This study utilizes 1D numerical modeling MIKE 11 with Hydrodynamic and Sediment Transport Modules. The hydrodynamic modeling inputs are river network and cross-sectional profiles. Hydrographs with return periods of 2, 5, 10, and 25 years are used as upstream boundaries, and a discharge curve is used as the downstream boundary of the model. The model is calibrated using water surface elevation measurements taken from September 13-16, 2021. The hydrodynamic modeling results indicate that Citarum Hilir and Cibeet Rivers cannot convey flood discharges with a 2-year return period. The sediment transport modeling results show no significant changes in the riverbed of Citarum Hilir before the confluence, but degradation of approximately 0.38 – 0.46 meters occurs after the confluence. Degradation happens in zones of maximum velocity where flow turbulence and shear stress increase, causing erosion of the Citarum Hilir riverbed. Degradation also occurs near the Cibeet River confluence due to flow acceleration at the outer bend of the river. Flooding and sediment transport are natural factors that can alter the morphology of river confluences, such as the confluence of Citarum Hilir and Cibeet Rivers.Keywords: Citarum river, Cibeet river, river confluence, hydrodinamic modeling, sedimen transport modeling